2
$\begingroup$

I am looking for a way to understand the last steps found at this site: http://mathdl.maa.org/mathDL/46/?pa=content&sa=viewDocument&nodeId=196&bodyId=203

The page finishes with showing in the modern style of Apollonius ellipse equation as

$$ y^2=x \left( p-\frac{p}{2a}x \right) $$

together with the comment: "Can this be written in the standard form of an ellipse? Complete the square and see."

I try to get this to the standard form as in: $$ \frac{y^2}{a^2}+\frac{x^2}{b^2}=1 $$

But the closest my algebra gets me is: $$ \frac{y^2}{xp}+\frac{x}{2a}=1 $$

Can anyone show me how they are connected?

$\endgroup$
1
  • $\begingroup$ You need the standard form $(y-y_0)^2/a^2+(x-x_0)^2/b^2=1$ instead. This is the equation of an (axis-aligned) ellipse centered at $(x_0,y_0)$ instead of at the origin. $\endgroup$
    – user856
    Nov 1, 2012 at 22:02

1 Answer 1

2
$\begingroup$

$$ y^2=x \left( p-\frac{p}{2a}x \right)$$

$$2a\cdot y^2=p(2ax-x^2)=-p\{(x-a)^2-a^2\}$$

$$2a\cdot y^2+p(x-a)^2=p\cdot a^2$$

$$\frac{(x-a)^2}{a^2}+\frac{y^2}{\frac{pa}2}=1$$

$$\left(\frac{x-a}a\right)^2+\left(\frac y{\sqrt\frac{pa}2}\right)^2=1$$

$\endgroup$
1
  • $\begingroup$ Thank you! I thought there was a error in your calculations first therefore i made an edit but i was wrong. (Is there any way for me to cancel my edit?) $\endgroup$ Nov 4, 2012 at 12:43

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .